Managing customer trust, satisfaction, and loyalty through information communication technologies - Eid, Riyad. (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2013)
"This book highlights technology's involvement with business processes in different sectors and industries while identifying marketing activities that are affected by its usage"--Provided by publisher.